Instituições de ensino superior e desenvolvimento: o caso do programa REUNI - Brüne, Sabrina (2015)
The main objective of this research was to analyze direct and indirect impacts generated by the adherence to the REUNI program at UFPR Palotina and UTFPR Toledo; as well as their spreading effects and influences on local development of the cities that host the universities. The justification was guided by the current discussion about federal public higher education in Brazil, and by the lack of studies about REUNI, when analyzed from the perspective of its interference potential in the urban space and local development. The research started with the assumption that the path the higher education policy took from 1990 contributed to mold the university role towards the development and, thereafter, a public university may be sufficient factor to alter the urban dynamics and local development. It was productive to examine the education policy path, the literature about the impact of higher education in development, conceptions of development, of public policy and educational policy, in order to understand the scenario that led to the viability of the program. To empirically understand the problem, a comparative case study between two institutions located in West Paraná, the Federal University of Paraná, campus Palotina (UFPR) and the Federal Technological University of Paraná, campus Toledo, whose adherence to the REUNI provoked institutional changes that were responsible for triggering demands for physical expansion and population growth, which, in their turn, printed alteration in the dynamic of the cities. To capture these changes, the primary data collection instrument was a questionnaire, applied to samples of the academic population (students, administrative technicians and professors, on both campuses). The questionnaires collected information categorized as' direct economic impacts (quantitative effects), regarded to the monthly income that was available and to the monthly expenses of students and federal employees due to consumption and staying in the city for study/work. The categorization of 'indirect economic impacts' used qualitative variables, such as: perception of changes in the urban environment, retention of graduates in the region and performance of the institution and the academic community in research and extension. The method of analysis was essentially qualitative and, the description of the results adopted the descriptive and interpretive method. Altogether, it was endorsed that the universities produced immediate economic effects, materialized into encouraging dynamism of the economy of the cities of Palotina and Toledo, mainly due to the income injection from academic and employees. More subtle effects related to urban development have also been identified. This study registries contributions to the institutions and cities from the effects emanating by the REUNI program, which was designed as an internalization strategy of public higher education and, when allocating institutions in areas that differ from the traditional central areas, it was responsible for promoting social access and inclusion and for triggering economic demands which were unlikely to be engendered without the push of a public policy.